Fra fængsel til samfund: Træning af servicehunde i et lukket fængsel - Kjær Minke, Linda (Nordisk Tidsskrift for Kriminalvidenskab, 2025)
Abstract Drawing on 28 qualitative interviews and observational data this study explores the Danish Dogs Behind Bars programme and its influence on incarcerated individuals and the prison environment. Six key themes emerged from the analysis: normalisation, responsi bility, trust, mental well-being, personal development and generativity. Findings reveal that the presence of dogs fosters a more humane and homelike atmosphere, supporting the normalisation of prison life. Both inmates and staff report that participation in the dog program fosters a range of positive outcomes: Inmates caring for dogs develop responsibility, self-discipline, and emotional stability, which can contribute to their personal growth and rehabilitation. It offers meaningful activities that foster self-confidence, optimism, and a sense of generativity. Trust is cultivated through the delegation of responsibility, enabling participants to feel valued and respected. The dogs also enhance mental well-being by providing emotional support, reducing stress, and encouraging positive social interactions, thereby improving both individual mental health and the overall prison climate. The program may have the potential to mitigate some of the negative effects of prisonisation by encouraging prosocial attitudes and behaviours. However, a key limitation lies in the strict selection criteria: participants must be well-behaved, drug-free. Furthermore, many already have prior experience with dog care. These factors may influence the programme’s outcomes and should be considered when assessing its broader applicability.